Rekayasa Media Pembelajaran Rantai Makanan Pada Hewan Menggunakan Augmented Reality - WARDANA, DEWANGGA WISNU, Hernawan Sulistyanto, S.T., M.T (2017)
The food chain is the transfer of energy from the organism at a trophic level to the next trophic level in the event of eating and being eaten by a certain order. The food chain is conceptually structured in trophic levels. According to Kaufmann (2002), augmented reality technology can be utilized as an interesting learning media. One of them is to design and build educational applications by applying the Augmented Reality technology in mobile android-based application with the method SDLC (System Development Life Cycle). Making an application using Unity3D software and Vuforia Augmented Reality SDK in building, and Blender software in the manufacturing of three dimensional objects. In this application also included exercises in order to increase understanding of the user in understanding the food chain. Results of research applications that are tested to elementary school students MI AL-ISLAM Grobagan with students demonstrating and directly operate the application. Based on data from the questionnaire, the introduction of augmented reality applications instructional media food chain can attract and help students in studying the food chain with the test results 81% of students expressed a clear and attractive main menu and 87% of students said that the application is able to increase the desire to learn. Then, students completed the answer after running these applications with significant value. With incrase about 53% from 20% to 70%.